KOMUNIKASI POLITIK ANGGOTA DEWAN: STUDI KASUS STRATEGI KOMUNIKASI POLITIK LISDA HENDRAJONI - Muhamad Nurobby, (2022)
The study of political communication has now become a subject of much discussion for the general public. In this paper, we will examine the strategies that were carried out by members of the Lisda Hendrajoni council during the 2019 campaign using the popular approach.